PENGARUH MOTIVASI DAN KUALITAS KEHIDUPAN KERJA TERHADAP KOMITMEN ORGANISASIONAL DAN DAMPAKNYA PADA KINERJA (Studi Pada RSUD. M Ashari Kabupaten Pemalang) - Mohamad Adibyo, 1352020047 (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study examines the influence of motivation, quality of work life against organizational commitment and its impact on performance. In this study involved 142 people respondents, all of which are composed of Personnel of nursing, Midwifery, Keteknisian Medical Personnel, medical personnel, Power Kefarmasian, Power in public administration/other Nutritional, energy and energy Keterapian of CIVIL SERVANTS and the PTT in the RSUD dr M Ashari Gen. Pemalang. Method of data collection is done using a questionnaire that is a collection of data by providing or distributing a list of questions to respondents in the hope of providing a response on the basis of those questions. This technique is used for primary data retrieval. Data collection in the study wore a questionnaire which is the technique of data collection is done by giving a set of questions or a question in writing to the respondent to be answered. Konfirmatori factor analysis results prove that all the indicators of each variable is able to explain motivation, quality of life variables work towards organizational commitment and its impact on performance. The results of the analysis of the distribution of the questionnaire found that motivation does not influence on organizational commitment, the quality of working life and organizational commitment affect, motivation and quality of work life influence on organizational commitment and impact on performance.Keywords: Motivation, Quality of Work Life, Commitment, Organizational Performance Â